KESIAPAN MAHASISWA DALAM IMPLEMENTASI PEMBELAJARAN AKTIF KONSTRUKTIF - Wagiran Wagiran (Universitas Negeri Yogyakarta, 2005)
Abstract This research was studying students’ readiness and expectation to the implementation of “constructive active learning”, teaching strategy, to support the competency-based curriculum. A survey with quantitative approach was conducted to third semester students at the Technical Engineering Teaching Education Study Program, Faculty of Engineering, UNY. With simple random sampling technique there were 197 samples of students. Data collecting with questionnaire have been tested its’ validity by rational judgment and validity of construct through with factor analysis. Reliability calculated with Alpha formula of Cronbach. Data analyzed with descriptive analysis. Result of research indicate that: 1) Student expectation to constructive active study according to study demand in applying of competence based curriculum is included at medium-high category with average 111.24 and attainment of score equal to 77.25% 2) Readiness of student in constructive active study according to study demand in applying of competence-based curriculum is included medium-high category with average 147.42 and attainment of score equal to 72.26%. therefore competent active study could be applied, but need efforts to improve of the readiness of student in learning. Keywords: active learning, competence-based curriculum, readiness of study